Toward Sustainable Development - Alam-, M (Elsevier, 2024)
Water is not only the end goal regarding safe drinking water and sanitation facilities (SDG 6), but also the critical means by which several other goals such as sustainable development goals (SDGs) of the 2030 Agenda for Sustainable Development can be achieved. It contributes to better health, gender equality, and improved quality of life. Sustainable water sources and infrastructure are crucial for ensuring that everyone can access clean drinking water, thereby improving health, reducing waterborne diseases, and promoting social equity. For access to adequate and equitable sanitation and hygiene, focusing on women and vulnerable groups, water is indispensable. Access to clean water ensures the functionality of sanitation facilities like toilets and handwashing stations, enabling proper hygiene practices, which, in turn, reduces disease transmission and addresses gender-specific needs, particularly for women and girls who often bear the responsibility for water collection and sanitation management. Accordingly, water is the linchpin for achieving SDG targets 6.a and 6.b. © 2024 Elsevier Inc. All rights are reserved including those for text and data mining AI training and similar technologies.